Evaluation of biomolecular interactions and cytotoxic activity of organometallic binuclear Ru(II) complexes of ferrocenyl thiosemicarbazones - Khanvilkar, Priyanka; Dash, Soumya R.; Vohra, Alisagar; Devkar, Ranjitsinh; Chakraborty, Debjani (Journal of Biomolecular Structure & Dynamics, 2020)
{Four new ferrocenyl substituted thiosemicarbazone ligands (L1-L4) and their corresponding binuclear ruthenium(II) arene complexes of the general type [(eta(6)-pcym)(L)Ru(mu-im)Ru(L)(eta(6)-p-cym)]Cl (C1-C4) and [(eta(6)-pcym)(L)Ru(mu-azpy)Ru(L)(eta(6)-p-cym)]Cl-2(C5-C8) (cym = cymene
Keywords: binuclear ruthenium(II) complexes; BSA binding interactions; DNA; Ferrocenyl thiosemicarbazone; HeLa human cervical carcinoma